Silicon nitride powder and method for producing same, and silicon nitride sintered compact and method for producing same

By sintering chromium- or nickel-containing metallic silicon powder in a nitrogen and hydrogen atmosphere, silicon nitride powder with high α-saturation rate is produced, solving the problem of large quality deviation of silicon nitride powder in the prior art and improving the mechanical properties and uniformity of silicon nitride sintered bodies.

CN120916972APending Publication Date: 2025-11-07DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480020343.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-22
Filing Date
2024-03-11
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing technologies make it difficult to efficiently manufacture silicon nitride powder and sintered bodies with high alpha saturation and small quality deviations, which affects their application in industrial equipment such as die casting machines and melting furnaces.

Method used

Silicon nitride powder is produced by firing metallic silicon powder containing chromium or nickel in a nitrogen and hydrogen atmosphere through a continuous furnace. The nitriding reaction conditions are controlled to improve the α-oxidation rate and uniformity, and reduce quality deviation.

Benefits of technology

This technology enables the efficient manufacturing of silicon nitride powder with high α-saturation, reduces the quality deviation of sintered bodies, and improves the mechanical properties and uniformity of silicon nitride sintered bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005604140040000191
    Figure BDA0005604140040000191
  • Figure BDA0005604140040000192
    Figure BDA0005604140040000192
  • Figure BDA0005604140040000201
    Figure BDA0005604140040000201
Patent Text Reader

Abstract

This silicon nitride powder contains a silicon nitride component having an alpha ratio of 90.0% or more and at least one component selected from the group consisting of a chromium-containing component and a nickel-containing component. The silicon nitride powder satisfies one or both of 50 [mu] g / g to 250 [mu] g / g of the chromium-containing component in terms of Cr and 5 [mu] g / g to 60 [mu] g / g of the nickel-containing component in terms of Ni.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a silicon nitride powder and a method for producing the same, and a silicon nitride sintered body and a method for producing the same. BACKGROUND

[0002] The silicon nitride sintered body is a material excellent in strength, hardness, toughness, heat resistance, corrosion resistance, heat shock resistance, and the like, and is thus used for various industrial parts such as die casting machines and melting furnaces, and insulating substrates for automobile parts. As a silicon nitride powder that is a raw material of the silicon nitride sintered body, a silicon nitride powder having a high α conversion rate is used in order to obtain a sintered body of high quality.

[0003] In Patent Literature 1, a silicon nitride powder having a high α conversion rate is attempted to be produced using a continuous fluidized bed reactor in order to improve productivity. In this Patent Literature 1, a metal silicon powder having a total content of metal impurities of 1.3% by mass or less and a content of Fe of 0.3% by mass or less is proposed as a raw material.

[0004] PRIOR ART

[0005] Patent Literature 1: Japanese Patent Application Laid-Open No. 2000-335907 SUMMARY

[0006] In the present application, a silicon nitride sintered body in which a variation in quality is sufficiently reduced and a method for producing the same are provided. The present application provides a silicon nitride powder excellent in sinterability and in which a variation in quality is sufficiently reduced. The present application provides a method for producing a silicon nitride powder excellent in sinterability and in which a variation in quality is sufficiently reduced, which can efficiently produce the silicon nitride powder.

[0007] One aspect of the present application provides a silicon nitride powder described below.

[0008] [1] A silicon nitride powder comprising: a silicon nitride component having an α conversion rate of 90.0% or more, and at least one selected from the group consisting of a chromium-containing component and a nickel-containing component,

[0009] The above silicon nitride powder satisfies one or both of the following conditions: the Cr conversion content of the above chromium-containing component is 50 μg / g to 250 μg / g; and the Ni conversion content of the above nickel-containing component is 5 μg / g to 60 μg / g.

[0010] The above silicon nitride powder of [1] has a high α conversion rate, and thus is excellent in sinterability. In addition, since the chromium-containing component and / or the nickel-containing component are contained in a trace amount, the nitriding reaction is performed with high uniformity at the time of production, and a variation in quality is sufficiently reduced. If this silicon nitride powder is used as a sintering raw material, for example, a silicon nitride sintered body in which a variation in quality is sufficiently reduced can be obtained. However, the use of the silicon nitride powder is not limited to the production of the silicon nitride sintered body.

[0011] The silicon nitride powder of the above [1] can be the following [2] or [3].

[0012] [2] The silicon nitride powder as recited in [1], wherein the average particle diameter is 0.5 to 2.0 μm, and the BET specific surface area is 5 to 15 m 2 / g.

[0013] [3] The silicon nitride powder as recited in [1] or [2], wherein the total value of the content of Cr converted from the chromium-containing component and the content of Ni converted from the nickel-containing component is 30 μg / g to 300 μg / g.

[0014] The silicon nitride powder of the above [2] has sufficiently excellent sinterability, and can sufficiently suppress abnormal grain growth. The silicon nitride powder of the above [3] performs a nitriding reaction with higher uniformity at the time of production. Therefore, the deviation in quality is further reduced. In addition, the performance of silicon nitride as it is can be sufficiently maintained. Therefore, if used as a sintering raw material, the deviation in quality is further reduced, and a silicon nitride sintered body having excellent performance can be obtained.

[0015] One aspect of the present application provides a production method of the following silicon nitride powder.

[0016] [4] A production method of a silicon nitride powder, having the step of firing a raw material powder containing a metallic silicon powder having an average particle diameter of 15 μm to 30 μm using a continuous furnace in an atmosphere containing nitrogen and hydrogen, to obtain a calcined body containing a silicon nitride component having an α conversion rate of 90.0% or more,

[0017] The above raw material powder contains at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, and satisfies one or both of the content of Cr converted from the chromium-containing component being 100 μg / g to 1000 μg / g and the content of Ni converted from the nickel-containing component being 50 μg / g to 1000 μg / g,

[0018] The ratio of the nitrogen in the above atmosphere is 95.1% by volume or more, and the ratio of the hydrogen in the above atmosphere is 2.0% by volume or more.

[0019] In the production method of the silicon nitride powder of the above [4], since a raw material powder containing a prescribed amount of at least one selected from the group consisting of a chromium-containing component and a nickel-containing component is used, the nitriding reaction is promoted. Therefore, a silicon nitride powder having excellent sinterability and a sufficiently reduced deviation in quality can be efficiently produced using a continuous furnace.

[0020] The production method of the above [4] can be the following [5] or [6].

[0021] [5] The method for producing a silicon nitride powder according to [4], wherein the silicon nitride powder obtained by pulverizing the calcined body in the continuous furnace in which the raw material powder filled in the container is calcined contains at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, and satisfies one or both of a Cr-converted content of the chromium-containing component of 50 μg / g to 250 μg / g and a Ni-converted content of the nickel-containing component of 5 μg / g to 60 μg / g.

[0022] [6] The method for producing a silicon nitride powder according to [4] or [5], wherein the raw material powder is heated to 1100°C or higher in the continuous furnace for 24 hours or less.

[0023] In the production method of [5], a silicon nitride powder having excellent sinterability and a sufficiently reduced variation in quality can be obtained. In the production method of [6], a silicon nitride powder having the above-described characteristics can be more efficiently produced.

[0024] One aspect of the present application provides the following silicon nitride sintered body.

[0025] [7] A silicon nitride sintered body containing at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, the silicon nitride sintered body satisfying one or both of a Cr-converted content of the chromium-containing component of 10 μg / g to 220 μg / g and a Ni-converted content of the nickel-containing component of 1 μg / g to 60 μg / g, wherein a Weibull coefficient is 9 or more.

[0026] Since the silicon nitride sintered body of [7] contains a prescribed amount of at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, the uniformity of the particles constituting the silicon nitride sintered body is high. Therefore, a variation in quality can be sufficiently reduced. The Weibull coefficient of the silicon nitride sintered body of [7] is 9 or more, and therefore a variation in bending strength is also sufficiently small.

[0027] The silicon nitride sintered body of [7] can be the following [8].

[0028] [8] The silicon nitride sintered body according to [7], wherein a total value of a Cr-converted content of the chromium-containing component and a Ni-converted content of the nickel-containing component is 20 μg / g to 300 μg / g.

[0029] One aspect of the present application provides the following method for producing a silicon nitride sintered body.

[0030] [9] A method for producing a silicon nitride sintered body, comprising: obtaining a silicon nitride sintered body by sintering a sintering raw material, the sintering raw material containing the silicon nitride powder described in any one of [1] to [3] or the silicon nitride powder obtained by the production method described in any one of [4] to [6].

[0031] The silicon nitride sintered body of the above [9] can improve the uniformity of the particles constituting the silicon nitride sintered body because the sintering raw material contains the silicon nitride powder described above or the silicon nitride powder obtained by the production method described above. Therefore, the quality deviation can be sufficiently reduced.

[0032] The present application can provide a silicon nitride sintered body whose quality deviation is sufficiently reduced and a production method thereof. The present application can provide a silicon nitride powder which is excellent in sinterability and whose quality deviation is sufficiently reduced. The present application can provide a production method of a silicon nitride powder which can efficiently produce a silicon nitride powder which is excellent in sinterability and whose quality deviation is sufficiently reduced. DETAILED DESCRIPTION

[0033] Embodiments of the present application are described below. However, the following embodiments are examples for illustrating the present application, and are not intended to limit the present application to the following content. In addition, in the present embodiments, a numerical range exemplified in the form of "a to b" is a numerical range in which the lower limit is a and the upper limit is b, and includes the numerical range of a and b. Values obtained by replacing the upper limit or the lower limit of each numerical range with a value of any one of the embodiments, and values obtained by replacing the upper limit or the lower limit of each numerical range with a value of another numerical range are also included in the present application.

[0034] The silicon nitride powder (Si3N4 powder) of one embodiment contains a silicon nitride component having an α conversion rate of 90.0% or greater, and at least one selected from a chromium-containing component and a nickel-containing component. The silicon nitride powder can contain the silicon nitride component and only the chromium-containing component or only the nickel-containing component, or can contain the silicon nitride component and both the chromium-containing component and the nickel-containing component.

[0035] The silicon nitride powder contains the silicon nitride component as a main component. The content of the silicon nitride component in the silicon nitride powder can be 90% by mass or greater, 95% by mass or greater, 98% by mass or greater, or 99% by mass or greater. The content of the silicon nitride component in the silicon nitride powder can be measured using a commercially available X-ray diffractometer.

[0036] The α-ratio of the silicon nitride component (the ratio of α-Si3N4to the entire Si3N4) is 90.0% or more. Such a silicon nitride powder has excellent sinterability, and thus has excellent mechanical properties when used as a sintering raw material, and a silicon nitride sintered body having a sufficiently reduced variation in quality can be obtained. From the viewpoint of improving the bending strength of the silicon nitride sintered body, the α-ratio of the silicon nitride component can be 91.0% or more, 92.0% or more, or 93.0% or more. From the viewpoint of reducing the manufacturing cost of the silicon nitride powder, the α-ratio of the silicon nitride component can be 98.0% or less, 97.0% or less, or 96.5% or less. One example of the α-ratio of the silicon nitride component is 90.0 to 98.0%. The α-ratio of the silicon nitride component can be obtained by the method described in the examples.

[0037] The chromium-containing component in the silicon nitride powder can be a chromium compound such as chromium oxide or chromium nitride, or can be elemental chromium (metallic chromium). The nickel-containing component in the silicon nitride powder can be a nickel compound such as nickel oxide or nickel nitride, or can be elemental nickel (metallic nickel). The chromium-containing component and the nickel-containing component can be contained in the metal silicon particles, or can be components that are intentionally added to the raw material powder before firing, or components that are mixed in during the manufacturing process.

[0038] The chromium-containing component in the silicon nitride powder is the content in terms of Cr (hereinafter, also referred to as "Cr content"). It can be 50 to 250 μg / g. Such a silicon nitride powder has a narrow distribution of composition because nitriding is sufficiently performed. Therefore, a silicon nitride sintered body having a sufficiently reduced variation in quality can be obtained. The Cr content in the silicon nitride powder can be 240 μg / g or less, 200 μg / g or less, or 190 μg / g or less. Thus, the original characteristics of the silicon nitride can be more sufficiently maintained. The Cr content in the silicon nitride powder can be 60 μg / g or more, 70 μg / g or more, or 80 μg / g or more. Such a silicon nitride powder is further nitrided, and thus a silicon nitride sintered body having a further reduced variation in quality can be obtained.

[0039] The nickel-containing component in the silicon nitride powder is the content in terms of Ni (hereinafter, also referred to as "Ni content"), and can be 5 to 60 μg / g. Such a silicon nitride powder has a narrow distribution of composition because nitriding is sufficiently performed. Therefore, a silicon nitride sintered body having a sufficiently reduced variation in quality can be obtained. The Ni content in the silicon nitride powder can be 50 μg / g or less, 40 μg / g or less, or 30 μg / g or less. Thus, the original characteristics of the silicon nitride can be more sufficiently maintained. The Ni content in the silicon nitride powder can be 7 μg / g or more, 8 μg / g or more, or 10 μg / g or more. Such a silicon nitride powder is further nitrided, and thus a silicon nitride sintered body having a further reduced variation in quality can be obtained.

[0040] The silicon nitride powder containing both the chromium-containing component and the nickel-containing component need not satisfy the above-mentioned numerical range of both the Cr content and the Ni content, but need only satisfy the numerical range of at least one of the Cr content and the Ni content. From the viewpoint of making the silicon nitride powder produced more uniformly promote nitriding, the total (Cr+Ni content) of the Cr content and the Ni content in the silicon nitride powder can be 35 μg / g or more, 40 μg / g or more, or 50 μg / g or more. From the viewpoint of sufficiently maintaining the original properties of the silicon nitride, the Cr+Ni content can be 280 μg / g or less, 240 μg / g or less, or 200 μg / g or less. An example of the range of the Cr+Ni content is 30 μg / g to 300 μg / g.

[0041] The Cr content and the Ni content in the silicon nitride powder can be quantified by ICP emission spectrometry. As a measuring device, for example, ICPE-9000 (device name, manufactured by Shimadzu Corporation) can be used.

[0042] The silicon nitride powder of the present embodiment contains a silicon nitride component with a high α conversion rate, and contains at least one of a chromium-containing component and a nickel-containing component in a prescribed amount. Nitriding of such a silicon nitride powder is sufficiently performed, and thus the composition has a small deviation. Therefore, if used as a sintering raw material, a silicon nitride sintered body with a sufficiently reduced deviation in quality can be obtained. In addition, the use of the silicon nitride powder is not limited to use for producing a silicon nitride sintered body, and for example, the silicon nitride powder can be mixed with other kinds of powder (for example, ceramic powder such as boron nitride) to produce a composite.

[0043] The silicon nitride powder can contain components other than the silicon nitride, the chromium-containing component, and the nickel-containing component. As such components, a calcium-containing component, a halogen, an iron-containing component, and the like can be given. The calcium-containing component and the halogen (fluorine) can be derived from fluorite used when synthesizing the silicon nitride. The iron-containing component can come from metal silicon particles, manufacturing processes, and the like. Such a silicon nitride powder and a silicon nitride sintered body can use lower-cost raw materials and manufacturing processes, and thus can reduce manufacturing costs.

[0044] The average particle diameter of the silicon nitride powder can be 0.5 to 2.0 μm. Such a silicon nitride powder has sufficiently excellent sinterability, and can sufficiently suppress abnormal grain growth at the time of sintering. The upper limit of the average particle diameter of the silicon nitride powder can be 1.6 μm, 1.4 μm, 1.2 μm, or 1.0 μm. Thereby, abnormal grain growth at the time of sintering can be further suppressed. The lower limit of the average particle diameter of the silicon nitride powder can be 0.6 μm or 0.7 μm. Thereby, sinterability can be further improved.

[0045] The average particle diameter of each powder in the present specification is found based on the method described in JIS Z8825:2013 "Particle Size Analysis - Laser Diffraction · Scattering Method". In the particle size distribution (cumulative distribution) in which the horizontal axis is expressed on a logarithmic scale and the vertical axis is expressed on a frequency [volume %] basis, which is determined based on the above method, the particle diameter at which the cumulative value from the small particle diameter reaches 50% of the whole is taken as the average particle diameter (D50, median particle diameter). The measuring device can use the device described in the examples. The average particle diameter of the silicon nitride powder can be adjusted by changing the particle diameter of the raw material powder, the firing temperature and the firing time when the silicon nitride powder is manufactured, and the conditions when the calcined body is pulverized.

[0046] The BET specific surface area of the silicon nitride powder can be 5 to 15 m 2 / g. Such a silicon nitride powder has sufficiently excellent sinterability, and can sufficiently suppress abnormal grain growth. The upper limit of the BET specific surface area of the silicon nitride powder can be 14 m 2 / g or 13 m 2 / g. Thereby, the sinterability can be further improved. The lower limit of the BET specific surface area of the silicon nitride powder can be 6 m 2 / g or 7 m 2 / g. Thereby, the abnormal grain growth at the time of sintering can be further suppressed.

[0047] The BET specific surface area of each powder in the present specification is a value determined by the BET one-point method using nitrogen gas in accordance with the method described in JIS Z8830:2013 "Determination of Specific Surface Area of Powders (Solids) Based on Gas Adsorption". The BET specific surface area of the silicon nitride powder can be adjusted by changing the particle diameter of the raw material powder, the firing temperature and the firing time when the silicon nitride powder is manufactured.

[0048] The manufacturing method of the silicon nitride powder of one embodiment has a step of firing a raw material powder containing a silicon metal powder in an atmosphere containing nitrogen and hydrogen using a continuous furnace to obtain a calcined body containing a silicon nitride component having an α conversion rate of 90.0% or more. The above-described silicon nitride powder can be manufactured by this manufacturing method. Therefore, the contents described in the embodiments of the silicon nitride powder also apply to this manufacturing method.

[0049] As the metal silicon powder, a powder obtained by pulverizing metal silicon particles (or blocks) can be used. As the pulverizing device, a hammer mill, a pin mill, a ball mill, a vibration mill, a bead mill, a jet mill, and the like can be cited. The average particle diameter (median particle diameter, D50) of the metal silicon powder can be 15 μm to 30 μm. From the viewpoint of smoothly performing nitriding, the average particle diameter of the metal silicon powder can be 28 μm or less, 26 μm or less, or 24 μm or less. If the raw material is nitrided in a powder state, excessive heat generation sometimes occurs. From the viewpoint of suppressing such heat generation, the average particle diameter of the metal silicon powder can be 16 μm or more or 18 μm or more. The average particle diameter of the metal silicon powder can be measured by the same method as the average particle diameter of the silicon nitride powder.

[0050] The purity of the metal silicon powder can be 98 mass% or more or 99 mass% or more. The metal silicon powder can contain impurities mixed in at the time of pulverization with the pulverizing device in addition to impurities from the metal silicon particles.

[0051] The metal silicon powder can be directly used as the raw material powder, or the metal silicon powder can be blended with a powder containing at least one component selected from the group consisting of fluorite, metal chromium, a chromium compound, metal nickel, and a nickel compound to prepare the raw material powder. As the chromium compound and the nickel compound, oxides and nitrides, for example, can be cited. Further, an alloy powder (for example, stainless steel) containing a chromium component and a nickel component can be blended into the metal silicon powder to prepare the raw material powder.

[0052] The raw material powder contains a metal silicon component as a main component, and contains at least one selected from a chromium-containing component and a nickel-containing component as a subcomponent. The raw material powder can contain the metal silicon component, and either of the chromium-containing component and the nickel-containing component. The raw material powder can contain the metal silicon component, and both of the chromium-containing component and the nickel-containing component. The content of the metal silicon component in the raw material powder can be 95 mass% or more, 97 mass% or more, or 98 mass% or more. The content of the metal silicon component in the raw material powder can be measured using a commercially available fluorescent X-ray analysis device.

[0053] The Cr-conversion content of the chromium-containing component in the raw material powder (hereinafter, sometimes referred to as "Cr content"). It can be 100 to 1000 μg / g. Nitriding of such a raw material powder proceeds sufficiently smoothly. Therefore, a silicon nitride powder in which the deviation of the composition is sufficiently reduced can be obtained in a short time. If such a silicon nitride powder is used as a sintering raw material, a silicon nitride sintered body in which the deviation of the quality is sufficiently reduced can be obtained. The Cr content in the raw material powder can be 960 μg / g or less, 900 μg / g or less, or 850 μg / g or less. Thus, the silicon nitride powder obtained can more sufficiently maintain the original characteristics of silicon nitride. The Cr content in the raw material powder can be 150 μg / g or more or 190 μg / g or more. If such a raw material powder is used, nitriding can be more smoothly performed.

[0054] The Ni-conversion content of the nickel-containing component in the raw material powder (hereinafter, sometimes referred to as "Ni content"). It can be 50 μg / g to 1000 μg / g. Nitriding of such a raw material powder proceeds sufficiently smoothly. Therefore, a silicon nitride powder in which the deviation of the composition is sufficiently reduced can be obtained in a short time. If such a silicon nitride powder is used as a sintering raw material, a silicon nitride sintered body in which the deviation of the quality is sufficiently reduced can be obtained. The Ni content in the raw material powder can be 970 μg / g or less, 900 μg / g or less, 800 μg / g or less, 600 μg / g or less, or 500 μg / g or less. Thus, the silicon nitride powder obtained can more sufficiently maintain the original characteristics of silicon nitride. The Ni content in the raw material powder can be 60 μg / g or more, 80 μg / g or more, or 100 μg / g or more. If such a raw material powder is used, nitriding can be more smoothly performed.

[0055] The raw material powder containing both the chromium-containing component and the nickel-containing component need not satisfy both the above-mentioned numerical ranges of the Cr content and the Ni content, but only needs to satisfy at least one of the numerical ranges of the Cr content and the Ni content. From the viewpoint of further uniformly promoting nitriding, the total value of the Cr content and the Ni content (Cr + Ni content) in the raw material powder can be 160 μg / g or more, can be 170 μg / g or more, or 180 μg / g or more. From the viewpoint of sufficiently maintaining the original performance of silicon nitride, the Cr + Ni content can be 1800 μg / g or less, 1600 μg / g or less, 1400 μg / g or less, or 1100 μg / g or less. An example of the range of the Cr + Ni content is 150 to 2000 μg / g.

[0056] The Cr content and the Ni content in the raw material powder can be quantified by ICP emission spectrometry. As a measuring device, for example, ICPE-9000 (device name, manufactured by Shimadzu Corporation) can be used.

[0057] To promote nitriding of the silicon metal, the raw material powder can contain fluorite. The content of fluorite can be 0.2 to 3 parts by mass relative to 100 parts by mass of the silicon metal powder. From the viewpoint of sufficiently promoting nitriding of the silicon metal, the content of fluorite can be 0.5 parts by mass or more or 0.8 parts by mass or more relative to 100 parts by mass of the silicon metal powder. From the viewpoint of reducing the contents of Ca and F in the obtained silicon nitride powder, the content of fluorite can be 2 parts by mass or less or 1.5 parts by mass or less relative to 100 parts by mass of the silicon metal powder.

[0058] The raw material powder can contain a component other than the silicon metal component, the chromium-containing component, the nickel-containing component, and fluorite. As such a component, an iron-containing component or the like can be given. The iron-containing component can come from the silicon metal particles, the manufacturing process, or the like. Such a raw material powder can be produced at low cost, and thus the manufacturing cost of the silicon nitride powder and the silicon nitride sintered body can be reduced.

[0059] The raw material powder is fired using a continuous furnace to obtain a calcined body containing a silicon nitride component. The continuous furnace can be, for example, a container carrying type tunnel-type push-through furnace, a roller hearth kiln, or the like. If it is such a continuous furnace, a container in which the raw material powder is housed can be continuously heated in the furnace. Since firing can be performed without molding the raw material powder, the nitriding reaction proceeds efficiently. Thus, a calcined body containing a silicon nitride component can be obtained in a short time. The silicon nitride component contained in such a calcined body has a high α rate. The numerical value of the specific α rate is as described in the embodiment of the silicon nitride powder.

[0060] The container in which the raw material powder is filled can use a container of a material that does not deteriorate to a temperature of about 1500°C in an inert gas atmosphere. The container can use, for example, a carbon-made, alumina-made, or boron nitride-made container. The structure of the container is not particularly limited, and for example, a container having a housing portion that houses the raw material powder can be used. From the viewpoint of operability, a container main body having a recessed portion and a lid that covers the recessed portion of the main body portion can be provided. Alternatively, the containers can be stacked in multiple layers, and the upper container can be used as the lid of the lower container.

[0061] The maximum temperature at which the raw material powder housed in the container is fired in the continuous furnace is 1300 to 1500°C. The temperature is increased to such a temperature at a rate of 10 to 150°C / hour. For example, the temperature can be increased from 30°C to 1100°C at a rate of 50 to 150°C / hour, and the temperature can be increased from 1100°C to the maximum temperature at a rate of 10 to 40°C / hour. Thus, the exothermic reaction caused by nitriding of the raw material powder can be moderately controlled.

[0062] The atmosphere at the time of firing can contain nitrogen and hydrogen. From the viewpoint of promoting nitriding of the metal silicon, the ratio of nitrogen in the firing atmosphere is 95.1% by volume or more, and can be 96.0% by volume or more. From the viewpoint of reducing oxides such as SiO2 contained in the raw material powder and promoting nitriding, the ratio of hydrogen in the firing atmosphere is 2.0% by volume or more, and can be 3.0% by volume or more, or 4.0% by volume or more. An example of the ratio of nitrogen in the firing atmosphere is 95.1 to 98.0% by volume. An example of the ratio of hydrogen in the firing atmosphere is 2.0 to 4.9% by volume. The atmosphere at the time of firing can contain a gas other than nitrogen and hydrogen. As such a gas, argon can be given. The ratio (by volume) of each gas in the present specification is a value under standard conditions (0°C, 1 atm).

[0063] The time for heating the raw material powder to 1100°C or higher in the continuous furnace can be 24 hours or less, 22 hours or less, or 20 hours or less. Even if the heating time at high temperature is thus shortened, since the raw material powder contains a chromium-containing component and / or a nickel-containing component, nitriding proceeds smoothly. Therefore, a silicon nitride powder of sufficiently high purity can be obtained. The time for heating to 1100°C or higher can be 10 hours or more, or 12 hours or more. After reaching the maximum temperature in the continuous furnace, the temperature can be maintained for several hours, or the temperature can be immediately lowered. The rate of temperature decrease is not particularly limited, and for example, the temperature can be decreased at a rate of 10 to 200°C / hour. After reaching approximately 300°C or lower, the temperature can be decreased in the atmosphere. Until then, the temperature can be decreased in the above-described atmosphere.

[0064] The calcined body obtained by the above-described firing contains silicon nitride (a silicon nitride component) as a main component. If the calcined body is pulverized, a silicon nitride powder can be obtained. The composition and particle diameter of the silicon nitride powder are as described above. Pulverization can be performed using, for example, a coarse pulverizer, a wet-type pulverizer, a ball mill, a vibration mill, or the like. Since the silicon nitride component contained as a main component in the calcined body has a high α rate, the calcined body can be smoothly pulverized.

[0065] After pulverization, a treatment step can be performed as necessary. For example, the pulverized calcined body can be combined with hydrofluoric acid having a hydrogen fluoride concentration of 10 to 40% by mass, and impurities can be reduced. For example, the pulverized calcined body can be dispersed in hydrofluoric acid and treated. The hydrogen fluoride concentration in the hydrofluoric acid can be 15 to 30% by mass. The temperature of the hydrofluoric acid in the treatment step is, for example, 40 to 80°C. In addition, the time for which the silicon nitride powder is immersed in the hydrofluoric acid is, for example, 1 to 10 hours.

[0066] The silicon nitride sintered body of one embodiment can be obtained using the silicon nitride powder described above. The silicon nitride sintered body can be obtained by sintering a molded body of the silicon nitride powder. The silicon nitride sintered body includes a silicon nitride component as a main component and includes at least one selected from the group consisting of a chromium-containing component and a nickel-containing component as a subcomponent. The content of the silicon nitride component in the silicon nitride sintered body can be 90 mass % or more, 93 mass % or more, 95 mass % or more, or 97 mass % or more. The content of the silicon nitride component in the silicon nitride sintered body can be measured with a commercially available X-ray diffractometer.

[0067] The chromium-containing component in the silicon nitride sintered body can be a chromium compound such as chromium oxide or chromium nitride, or can be elemental chromium (metallic chromium). The nickel-containing component in the silicon nitride sintered body can be a nickel compound such as nickel oxide or nickel nitride, or can be elemental nickel (metallic nickel).

[0068] The content of the chromium-containing component in the silicon nitride sintered body in terms of Cr (hereinafter also referred to as "Cr content") can be 10 to 220 μg / g. Such a silicon nitride sintered body is obtained using a silicon nitride powder in which nitriding is sufficiently performed, and thus the uniformity of particles that constitute the silicon nitride sintered body is high. That is, the distribution of composition is sufficiently narrow. Thus, the variation in quality can be sufficiently reduced. The Cr content in the silicon nitride sintered body can be 180 μg / g or less, 170 μg / g or less, 160 μg / g or less, or 100 μg / g or less. Thus, the original characteristics of silicon nitride can be more sufficiently maintained. The Cr content in the silicon nitride powder can be 20 μg / g or more, 30 μg / g or more, or 40 μg / g or more. Such a silicon nitride sintered body is obtained using a silicon nitride powder in which nitriding is further performed, and thus the variation in quality can be further reduced.

[0069] The content of the nickel-containing component in the silicon nitride sintered body in terms of Ni (hereinafter also referred to as "Ni content") can be 1 to 60 μg / g. Such a silicon nitride sintered body is obtained using a silicon nitride powder in which nitriding is sufficiently performed, and thus the uniformity of particles that constitute the silicon nitride sintered body is high. That is, the distribution of composition is sufficiently narrow. Thus, the variation in quality can be sufficiently reduced. The Ni content in the silicon nitride sintered body can be 55 μg / g or less, 50 μg / g or less, or 45 μg / g or less. Thus, the original characteristics of silicon nitride can be more sufficiently maintained. The Ni content in the silicon nitride sintered body can be 5 μg / g or more, 10 μg / g or more, or 15 μg / g or more. Such a silicon nitride sintered body is obtained using a silicon nitride powder in which nitriding is further performed, and thus the variation in quality can be further reduced.

[0070] The silicon nitride sintered body containing both the chromium-containing component and the nickel-containing component does not need to satisfy both the numerical ranges of the Cr content and the Ni content described above, but only needs to satisfy at least one of the numerical ranges of the Cr content and the Ni content. From the viewpoint of further reducing the variation in the quality of the finished product, the total value of the Cr content and the Ni content (Cr+Ni content) in the silicon nitride sintered body can be 30 μg / g or more, can be 40 μg / g or more, 50 μg / g or more, or 60 μg / g or more. From the viewpoint of sufficiently maintaining the original properties of silicon nitride, the Cr+Ni content can be 280 μg / g or less, 260 μg / g or less, 240 μg / g or less, or 220 μg / g or less. An example of the range of the Cr+Ni content is 20 μg / g to 300 μg / g.

[0071] The chromium-containing component in the silicon nitride sintered body can be a chromium compound such as chromium oxide or chromium nitride, or can be elemental chromium (metallic chromium). The nickel-containing component in the silicon nitride sintered body can be a nickel compound such as nickel oxide or nickel nitride, or can be elemental nickel (metallic nickel). The chromium-containing component and the nickel-containing component can come from the silicon nitride powder or from the manufacturing process.

[0072] The Cr content and the Ni content in the silicon nitride sintered body can be quantified by ICP emission spectrometry. As a measuring device, for example, ICPE-9000 (device name, manufactured by Shimadzu Corporation) can be used.

[0073] The silicon nitride sintered body can contain components other than the silicon nitride, the chromium-containing component, and the nickel-containing component. As such components, components derived from a sintering aid and a ferrous component, etc. can be given. As the sintering aid, an oxide-based sintering aid such as Y2O3, MgO, and Al2O3 can be given. The content of the component derived from the sintering aid in the silicon nitride sintered body can be, for example, 3 to 10 mass%.

[0074] The Weibull coefficient (m) of the silicon nitride sintered body can be 9 or more, 10 or more, or 11 or more. Thereby, the variation in the quality can be sufficiently reduced. The Weibull coefficient (m) in the present specification is a shape parameter in JIS R1625:2010, and can be obtained by statistically processing the bending strength (σ). The single mode / binary Weibull distribution function (F(σ)) is represented by the following formula (1). In formula (1), σ is the bending strength measured in accordance with JIS R1601:2008, and η is a scale parameter. In a Weibull graph obtained in a graph in which the vertical axis is ln(ln(1 / (1-F(σ))) and the horizontal axis is lnσ, the Weibull coefficient m can be obtained as the slope of a straight line. The larger the Weibull coefficient m thus obtained, the smaller the variation in the bending strength. Therefore, the variation in the quality is reduced, and the reliability is excellent.

[0075] F(σ) = 1 - exp[-(σ / η)m]...(1)

[0076] The bending strength of the silicon nitride sintered body measured in accordance with JIS R1601:2008 can be 920 MPa or greater, 1000 MPa or greater, or 1050 MPa or greater. From the viewpoint of improving the bending strength, the relative density of the silicon nitride sintered body can be 97% or greater, or 98% or greater. From the viewpoint of improving the bending strength, the bulk density of the silicon nitride sintered body can be 3.1 g / cm3or greater, 3.2 g / cm3or greater, or 3.3 g / cm3or greater. The bulk density of the silicon nitride sintered body can be 3.4 g / cm3or less, 3.3 g / cm3or less, or 3.2 g / cm3or less. 3 The relative density and the bulk density of the silicon nitride sintered body in the present specification are measured by the Archimedes method.

[0077] The manufacturing method of the silicon nitride sintered body of one embodiment has a sintering step of molding and sintering a sintering raw material including the above-described silicon nitride powder as a main component. The sintering raw material can include an oxide-based sintering aid in addition to the silicon nitride powder. As the oxide-based sintering aid, Y2O3, MgO, Al2O3, and the like can be given. The content of the oxide-based sintering aid in the sintering raw material can be, for example, 3 mass% to 10 mass%.

[0078] In the above-described sintering step, the above-described sintering raw material is pressed at a molding pressure of, for example, 3.0 MPa to 200 MPa to obtain a molded body. The molded body can be manufactured by uniaxial pressing or by CIP. Alternatively, the sintering can be performed while being subjected to hot press molding. The sintering of the molded body can be performed in a non-active gas atmosphere such as nitrogen or argon. The pressure at the time of sintering can be 0.7 MPa to 1 MPa. The sintering temperature can be 1700 °C to 2100 °C, or 1800 °C to 2000 °C. The sintering time at the sintering temperature can be 2 hours to 20 hours, or 4 hours to 16 hours. The temperature increase rate up to the sintering temperature can be, for example, 1.0 °C / hour to 10.0 °C / hour. Thus, the silicon nitride sintered body can be obtained.

[0079] In the above-described manufacturing method, since the sintering raw material including the silicon nitride powder in which nitriding is sufficiently uniformly performed is used, the uniformity of the particles constituting the silicon nitride sintered body can be improved. That is, the distribution of the composition can be sufficiently narrowed. The variation in the quality of the silicon nitride sintered body is sufficiently reduced, and the reliability is excellent.

[0080] The above describes several embodiments, but the present application is not limited to any of the above-described embodiments.

[0081] Example

[0082] The content of the present application is described in more detail with reference to examples and comparative examples, but the present application is not limited to the following examples.

[0083] (Example 1)

[0084] <Preparation and evaluation of metal silicon powder>

[0085] A metal silicon block having a particle size of 10 to 50 mm was prepared. The metal silicon block was coarsely pulverized using a pulverizing device (device name: jaw crusher, Makino Co., Ltd.) and a pulverizing device (device name: roll crusher, Makino Co., Ltd.), and then finely pulverized using a pulverizing device (device name: vibration mill, Central Chemical Machine Co., Ltd.) to obtain a metal silicon powder. The pulverizing time of the vibration mill was 300 minutes. The particle size distribution of the metal silicon powder was measured. The particle size distribution was measured by a laser diffraction scattering method. Specifically, the measurement was performed in accordance with the method described in JIS Z8825:2013 “Particle Size Analysis - Laser Diffraction·Scattering Method”. The measurement of the particle size distribution was performed by weighing 60 mg of the metal silicon powder in a 500 mL container. A 20% aqueous solution (2 mL) of sodium hexametaphosphate as a dispersant and water (200 g) were added thereto. The container was set in an ultrasonic disperser (trade name: Sharp, Japan) so that the entire receiving portion of the dispersion liquid was immersed, and ultrasonic dispersion was performed for 1 minute. The sample after the ultrasonic dispersion was used for the measurement of the particle size distribution. The measurement of the particle size distribution was performed using LS13320 (trade name, Beckman Coulter Co., Ltd.). The average particle size (D50, median particle size) of the metal silicon powder is shown in Table 1.

[0086] <Preparation and evaluation of raw material powder>

[0087] A raw material powder was prepared by mixing and blending fluorite and nickel oxide powder (NiO) in the above-described metal silicon powder. The blending amount of fluorite was 1% by mass based on the metal silicon powder, and the blending amount of nickel oxide powder was 200 ppm by mass. The content of the chromium component converted to Cr (Cr content) and the content of the nickel component converted to Ni (Ni content) in the raw material powder thus prepared were measured by ICP emission spectrometry. As the measuring device, ICPE-9000 (trade name, Shimadzu Corporation) was used. The measurement results are shown in Table 1. The total value of the Cr content and the Ni content is also shown in Table 1.

[0088] <Preparation of silicon nitride powder>

[0089] A plurality of graphite containers having a recess were prepared. The raw material powder was filled in the recess of each of the plurality of containers. The size of each container was 300 mm x 300 mm x 70 mm. 1.4 kg of the raw material powder was filled in each container. The filling height H of the raw material powder in the recess was 30 mm. The container filled with the raw material powder was introduced into a container-transporting continuous furnace, and the metal silicon component contained in the raw material powder was nitrided.

[0090] In a continuous furnace, after 11 hours of temperature increase from room temperature to 1100°C and 18 hours of temperature increase from 1100°C to 1400°C in an atmosphere containing nitrogen and hydrogen. The ratio of nitrogen in the atmosphere was set to 96 vol%, and the ratio of hydrogen was set to 4 vol%. After temperature increase to 1400°C, cooling to 200°C was performed in the above atmosphere to obtain a calcined body containing silicon nitride as a main component. The time for heating the raw material powder to 1100°C or higher was 18 hours. Then, the calcined body was allowed to cool to room temperature in the atmosphere. After coarsely pulverizing the calcined body using a coarse pulverizing device (device name: jaw crusher, MAKINO Co., Ltd.) and a pulverizing device (device name: roll crusher, MAKINO Co., Ltd.), wet pulverization was performed using a ball mill to obtain a pulverized product. With respect to the wet pulverization, the filling rate of the balls with respect to the container was set to 60 vol%, water was used as a solvent, and the pulverization time was set to 10 hours (wet pulverization time). The above pulverized product obtained by wet pulverization was subjected to acid treatment by immersing in hydrofluoric acid (hydrofluoric acid concentration: 30 mass%) at a temperature of 70°C for 2 hours. Then, the pulverized product was taken out of the hydrofluoric acid, washed with water, and dried under a nitrogen atmosphere. Thus, a silicon nitride powder was obtained.

[0091] <Assessment of the silicon nitride powder>

[0092] The α rate of the silicon nitride component contained in the silicon nitride powder was determined in accordance with the following procedure. X-ray diffraction of the silicon nitride powder was performed using an X-ray diffractometer (Rikaku Co., Ltd., device name: Ultima IV) using CuKα rays. The α phase was represented by the diffraction line intensity I a102 of the (102) plane and the diffraction line intensity I a210 of the (210) plane. The β phase was represented by the diffraction line intensity I b101 of the (101) plane and the diffraction line intensity I b210 of the (210) plane. Using these diffraction line intensities, the α rate was calculated by the following formula. The results are shown in Table 1.

[0093] α rate (%) =

[0094] (I a102 + I a210 ) / (I a102 + I a210 + I b101 + I b210 ) x 100

[0095] The average particle diameter (D50, median particle diameter) and the BET specific surface area of the silicon nitride powder are shown in Table 1. The average particle diameter of the silicon nitride powder was determined by the same method as that for the silicon metal powder. The BET specific surface area of the silicon nitride powder was determined in accordance with JIS Z 8803:2013 using nitrogen by the BET one-point method.

[0096] The Cr-conversion content (Cr content) of the chromium-containing component and the Ni-conversion content (Ni content) of the nickel-containing component in the silicon nitride powder were determined by ICP emission spectrometry. As the measuring device, an ICPE-9000 (device name, manufactured by Shimadzu Corporation) was used. The results of the measurement are shown in Table 1. The total value of the Cr content and the Ni content thus determined is also shown in Table 1.

[0097] <Manufacture of silicon nitride sintered body>

[0098] The prepared silicon nitride powder 90 parts by mass, Y2O3 powder 5 parts by mass having an average particle diameter of 1.5 μm, and Al2O3 powder 4 parts by mass having an average particle diameter of 1.0 μm were mixed in ethanol for 4 hours. Then, the mixed powder thus dried was subjected to mold molding at a pressure of 10 MPa, and further subjected to CIP molding at a pressure of 100 MPa. The obtained molded body was disposed in a carbon-made crucible together with filler powder composed of a mixed powder of silicon nitride powder and BN powder, and fired in a nitrogen pressurized atmosphere at 1 MPa at a temperature of 1800°C for 4 hours to manufacture a silicon nitride sintered body.

[0099] <Evaluation of silicon nitride sintered body>

[0100] The three-point bending strength of the manufactured silicon nitride sintered body was measured. The measurement was performed in accordance with JIS R1601:2008 using a commercially available bending strength meter (manufactured by Shimadzu Corporation, device name: AG-2000). Twenty measurement samples were prepared and the measurement was performed (N=20). The Weibull plot of the measurement values was prepared in accordance with JIS R1625:2010, and the slope (m) of the graph in the Weibull plot was taken as the Weibull coefficient. The Weibull coefficient is shown in Table 1.

[0101] The Cr-conversion content (Cr content) of the chromium-containing component and the Ni-conversion content (Ni content) of the nickel-containing component in the silicon nitride sintered body were determined by ICP emission spectrometry after the silicon nitride sintered body was pulverized with a vibration mill. The results are shown in Table 1. The total value of the Cr content and the Ni content thus determined is also shown in Table 1.

[0102] (Example 2)

[0103] A metal silicon powder was prepared in the same procedure as in Example 1. Fluorite and chromium oxide powder (Cr2O3) were mixed and compounded in the metal silicon powder. The compounding amount of the fluorite was 1% by mass and the compounding amount of the chromium oxide powder was 220 mass ppm based on the metal silicon powder. Except for using the thus prepared raw material powder, a silicon nitride powder and a silicon nitride sintered body were prepared in the same procedure as in Example 1, and each evaluation was performed. The results are shown in Table 1.

[0104] (Example 3 to Example 4)

[0105] A metal silicon powder was prepared in the same procedure as in Example 1. Fluorite, chromium oxide powder (Cr203) and nickel oxide powder (NiO) were mixed in and with the metal silicon powder. In Example 3, the mixing amount of fluorite was 1 mass% and the mixing amount of chromium oxide powder was 1300 mass ppm and the mixing amount of nickel oxide was 1200 mass ppm, based on the metal silicon powder. In Example 4, the mixing amount of fluorite was 1 mass% and the mixing amount of chromium oxide powder was 90 mass ppm and the mixing amount of nickel oxide was 20 mass ppm, based on the metal silicon powder. Except for using the respective raw material powders thus prepared, silicon nitride powder and silicon nitride sintered bodies were prepared in the same procedure as in Example 1, and respective evaluations were performed. The results are shown in Table 1.

[0106] (Example 5 to Example 6)

[0107] A metal silicon powder was prepared in the same procedure as in Example 1. Fluorite, chromium oxide powder (Cr203) and nickel oxide powder (NiO) were mixed in and with the metal silicon powder. In Example 5 and 6, the mixing amount of fluorite was 1 mass% and the mixing amount of chromium oxide powder was 220 mass ppm and the mixing amount of nickel oxide was 80 mass ppm, based on the metal silicon powder. Except for using the raw material powders thus prepared, and except for setting the wet pulverization time of the calcined body at the time of preparing the silicon nitride powder to 6 hours in Example 5 and to 14 hours in Example 6, silicon nitride powder and silicon nitride sintered bodies were prepared in the same procedure as in Example 1, and respective evaluations were performed. The results are shown in Table 1.

[0108] (Example 7 and 8)

[0109] A metal silicon powder was prepared in the same procedure as in Example 1. Fluorite, chromium oxide powder (Cr203) and nickel oxide powder (NiO) were mixed in and with the metal silicon powder. The mixing amount of fluorite was 1 mass% and the mixing amount of chromium oxide powder was 220 mass ppm and the mixing amount of nickel oxide was 80 mass ppm, based on the metal silicon powder.

[0110] Except for using the raw material powders thus prepared, and except for setting the ratio of hydrogen gas in the atmosphere of the continuous furnace (the remaining portion being nitrogen gas) as shown in Table 2 at the time of preparing the silicon nitride powder, silicon nitride powder and silicon nitride sintered bodies were prepared in the same procedure as in Example 1, and respective evaluations were performed. The results are shown in Table 2.

[0111] (Example 9 to Example 11)

[0112] The metal silicon powder was prepared in the same manner as in Example 1. Fluorite and stainless steel powder (SUS304) were mixed in and with the metal silicon powder. In Example 9, the mixing amount of fluorite was 1 mass% and the mixing amount of stainless steel powder was 200 mass ppm, based on the metal silicon powder. In Example 10, the mixing amount of fluorite was 1 mass% and the mixing amount of stainless steel powder was 90 mass ppm, based on the metal silicon powder. In Example 11, the mixing amount of fluorite was 1 mass% and the mixing amount of stainless steel powder was 1300 mass ppm, based on the metal silicon powder. Except for using the respective raw material powders thus prepared, silicon nitride powder and silicon nitride sintered body were prepared in the same manner as in Example 1, and each evaluation was performed. The results are shown in Table 2.

[0113] (Example 12)

[0114] When the metal silicon powder was obtained from a metal silicon block, the pulverization time using a pulverization device (device name: vibration mill (manufactured by Chuo Sangyo Co., Ltd.)) was changed from 300 minutes to 420 minutes. Fluorite and stainless steel powder (SUS304) were mixed in and with the metal silicon powder thus obtained. The mixing amount of fluorite was 1 mass% and the mixing amount of stainless steel powder was 80 mass ppm, based on the metal silicon powder. Except for using the raw material powders thus prepared, silicon nitride powder and silicon nitride sintered body were prepared in the same manner as in Example 1, and each evaluation was performed. The results are shown in Table 2.

[0115] (Example 13)

[0116] When the metal silicon powder was obtained from a metal silicon block, the pulverization time using a pulverization device (device name: vibration mill (manufactured by Chuo Sangyo Co., Ltd.)) was changed from 300 minutes to 240 minutes. Fluorite and stainless steel powder (SUS304) were mixed in and with the metal silicon powder thus obtained. The mixing amount of fluorite was 1 mass% and the mixing amount of stainless steel powder was 1000 mass ppm, based on the metal silicon powder. Except for using the raw material powders thus prepared, silicon nitride powder and silicon nitride sintered body were prepared in the same manner as in Example 1, and each evaluation was performed. The results are shown in Table 3.

[0117] (Examples 14 to 16)

[0118] A metal silicon powder was prepared in the same procedure as in Example 1. One or both of a metal chromium powder (Cr) and a metal nickel powder (Ni) and fluorite were compounded in the metal silicon powder and mixed. In Example 14, the compounding amount of fluorite was 1 mass% and the compounding amount of the metal nickel powder was 150 mass ppm, based on the metal silicon powder. In Example 15, the compounding amount of fluorite was 1 mass% and the compounding amount of the metal chromium powder was 150 mass ppm, based on the metal silicon powder. In Example 16, the compounding amount of fluorite was 1 mass%, the compounding amount of the metal chromium powder was 150 mass ppm, and the compounding amount of the metal nickel was 50 mass ppm, based on the metal silicon powder. Except for using the raw material powder thus prepared, a silicon nitride powder and a silicon nitride sintered body were prepared in the same procedure as in Example 1, and each evaluation was performed. The results are shown in Table 3.

[0119] (Comparative Example 1)

[0120] A metal silicon powder was prepared in the same procedure as in Example 1. A raw material powder was prepared by compounding and mixing only fluorite in the metal silicon powder. Except for using the raw material powder thus prepared, a silicon nitride powder and a silicon nitride sintered body were prepared in the same procedure as in Example 1, and each evaluation was performed. The results are shown in Table 3.

[0121] (Comparative Example 2)

[0122] The pulverization time using a pulverization device (device name: vibration mill, manufactured by Chuo Sangyo Co., Ltd.) when a metal silicon powder was obtained from a metal silicon block was changed from 300 minutes to 210 minutes. Fluorite, a chromium oxide powder (Cr203), and a nickel oxide powder (NiO) were compounded and mixed in the metal silicon powder thus obtained. The compounding amount of fluorite was 1 mass% and the compounding amount of the chromium oxide powder was 220 mass ppm, and the compounding amount of the nickel oxide was 80 mass ppm, based on the metal silicon powder. Except for using the raw material powder thus prepared, a silicon nitride powder and a silicon nitride sintered body were prepared in the same procedure as in Example 1, and each evaluation was performed. The results are shown in Table 3.

[0123] Table 1

[0124]

[0125] Table 2

[0126]

[0127] Table 3

[0128]

[0129] The Weibull coefficient of the silicon nitride sintered body of Examples 1 to 16 is 9 or more, which is greater than that of Comparative Examples 1 and 2. It is thus confirmed that the silicon nitride sintered body of Examples 1 to 16 has less variation in the bending strength and sufficiently reduced variation in quality as compared with the silicon nitride sintered body of Comparative Examples 1 and 2.

[0130] Industrial applicability

[0131] The present application can provide a silicon nitride sintered body having sufficiently reduced variation in quality. The present application can provide a silicon nitride powder having excellent sinterability and sufficiently reduced variation in quality. The present application can provide a method for producing a silicon nitride powder, which can efficiently produce the above-described silicon nitride powder.

Claims

1. A silicon nitride powder comprising: a silicon nitride component having an α conversion rate of 90.0% or more, and at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, the silicon nitride powder satisfying one or both of: a Cr-conversion content of the chromium-containing component of 50 μg / g to 250 μg / g; and a Ni-conversion content of the nickel-containing component of 5 μg / g to 60 μg / g.

2. The silicon nitride powder according to claim 1, wherein an average particle diameter of 0.5 μm to 2.0 μm and a BET specific surface area of 5 m 2 / g to 15 m 2 / g.

3. The silicon nitride powder according to claim 1 or 2, wherein the total value of the Cr-conversion content of the chromium-containing component and the Ni-conversion content of the nickel-containing component is 30 μg / g to 300 μg / g.

4. A method for producing a silicon nitride powder, comprising the following steps: firing a raw material powder comprising a metallic silicon powder having an average particle diameter of 15 μm to 30 μm in an atmosphere containing nitrogen and hydrogen using a continuous furnace to obtain a calcined body comprising a silicon nitride component having an α conversion rate of 90.0% or more, the raw material powder comprising at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, and satisfying one or both of: a Cr-conversion content of the chromium-containing component of 100 μg / g to 1000 μg / g; and a Ni-conversion content of the nickel-containing component of 50 μg / g to 1000 μg / g, the ratio of the nitrogen in the atmosphere being 95.1% by volume or more, and the ratio of the hydrogen in the atmosphere being 2.0% by volume or more.

5. The method for producing a silicon nitride powder according to claim 4, wherein the silicon nitride powder obtained by crushing the calcined body, which is obtained by firing the raw material powder filled in a container in the continuous furnace, comprises at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, and satisfies one or both of: a Cr-conversion content of the chromium-containing component of 50 μg / g to 250 μg / g; and a Ni-conversion content of the nickel-containing component of 5 μg / g to 60 μg / g.

6. The method for producing a silicon nitride powder according to claim 4 or 5, wherein the time for which the raw material powder is heated to 1100°C or more in the continuous furnace is 24 hours or less.

7. A silicon nitride sintered body comprising at least one selected from the group consisting of a chromium-containing component and a nickel-containing component, the silicon nitride sintered body satisfying one or both of: a Cr-conversion content of the chromium-containing component of 10 μg / g to 220 μg / g; and a Ni-conversion content of the nickel-containing component of 1 μg / g to 60 μg / g, wherein a Weibull coefficient is 9 or more.

8. The silicon nitride sintered body according to claim 7, wherein the total value of the Cr-conversion content of the chromium-containing component and the Ni-conversion content of the nickel-containing component is 20 μg / g to 300 μg / g. a silicon nitride sintered body is obtained by firing a sintering raw material comprising the silicon nitride powder according to claim 1 or 2.

9. A method for producing a silicon nitride sintered body, comprising: ​

Citation Information

Patent Citations

  • Production of silicon nitride powder with high alpha-type content

    JP2000335907A